Atrazine, Clarity, Verdict, and Armezon Pro Application Timings for Weed Control in Fallow - R. Currie; P. Geier (Kansas Agricultural Experiment Station Research Reports, 2017)
A study was initiated near Garden City, KS, in 2016, comparing the weed control of several herbicide treatments and their time of application in fallow. A single application of Clarity (dicamba) and atrazine applied on March 3, 2016, did not provide more than 93% control of kochia, Russian thistle, and Palmer amaranth on June 9. All other treatments provided 95% or greater control at the evaluation conducted June 9. Three applications were needed to provide 90% or greater control of all three species through July 6.
Keywords: : single application; sequential applications